Lived experiences of women with co-existing BMI≥30 and Gestational Diabetes Mellitus. (June 2017) - Jarvie, Rachel
Abstract: Objective: to explore the lived experiences of women with co-existing maternal obesity (BMI ≥ 30) and Gestational Diabetes Mellitus (GDM) during pregnancy and the post-birth period (<3 months post-birth). Design: A qualitative, sociological design was utilised. Data were collected using a series of sequential in-depth narrative interviews during pregnancy and post-birth and fieldnotes. Cross sectional thematic analysis of the data set was undertaken, alongside the construction/analysis of in-depth biographical longitudinal case profiles of individual participants. Setting: Participants were recruited from diabetic antenatal clinics at two NHS hospital trusts in the South West of England.Participants: 27 women with co-existing BMI ≥ 30 and GDM. Participants were predominantly of low socio-economic status (SES). Findings: Women were experiencing a number of social and economic stressors that compromised their ability to manage pregnancies complicated by maternal obesity and GDM, and make lifestyle changes.Women perceived themselves to be stigmatised by healthcare professionals and the general public due to their obese and gestational diabetic status. Key conclusions: Women of low SES with maternal obesity and GDM perceived healthcare professionals' recommendations with respect to lifestyle change as unrealistic given their constrained social/material circumstances. Frequent references to weight/lifestyle change by different HCPs were seen as stigmatising and may be counterproductive. Implications for practice: Women would like more collaborative care which acknowledges/addresses their personal and financial circumstances. Multidisciplinary teams should give consideration to how, by whom, and the frequency with which issues of weight/lifestyle change are being discussed in order to avoid women feeling stigmatised. Highlights: Women with maternal obesity/GDM were predominantly of low socioeconomic status. Social/economic stressors compromised management of pregnancies/lifestyle change. Women want collaborative maternity care addressing their personal circumstances. Women perceived themselves to be stigmatised due to obesity and GDM. Frequent references to weight/lifestyle contributed to feelings of stigmatisation.